Role of Corporate Governance in Industries Facing Difference Levels of Competition: Empirical Evidence from Pakistan (Journal of Social Sciences Review, 2023)
The purpose of this study is to figure out the role of corporate governance in competitive industries and its impact along with product market competition on firm’s value. The sample of this study is obtained from the PSX-100 index, containing fifty-two non-financial firms from 2009 to 2018. This study documents the complementary association between competition in the product market and governance mechanisms. It concludes that good governance in Pakistani firms improves the value of the firm only in highly competitive industries, largely through mitigating the agency problem of empire-building. These findings are robust by employing alternate measures of sample division, firm governance structure, regression specifications, and ownership structure. Policymakers are required to focus governance policies mainly on the firms in highly competitive industries to get maximum progress. Moreover, they also need to improve anti-trust laws to increase the level of competition in all industries in the context of Pakistan.
Keywords: Corporate Governance; Product Competition; Firm value; Fixed Effects; Pakistan